R deep learning essentials : a step-by-step guide to building deep learning models using TensorFlow, Keras, and MXNet - Hodnett, Mark; Wiley, Joshua F. (Packt Publishing Ltd, 2018)
This book demonstrates how to use deep Learning in R for machine learning, image classification, and natural language processing. It covers topics such as convolutional networks, recurrent neural networks, transfer learning and deep learning in the cloud. By the end of this book, you will be able to apply deep learning to real-world projects.